Topical antibiotics in the dermatological clinical practice: Indications, efficacy, and adverse effects. Issue 6 (12th July 2020) - Bonamonte, Domenico; De Marco, Aurora; Giuffrida, Roberta; Conforti, Claudio; Barlusconi, Chiara; Foti, Caterina; Romita, Paolo
Abstract: Topical antibiotic therapy is a central component of patient management for several skin conditions, including acne, hidradenitis suppurativa, rosacea, impetigo or other superinfected dermatitis, and prevention of wound infections. Moreover, particular situations, such as skin diseases of bacterial origin in pregnancy and infants often warrant topical therapy. However, the occurrence of local delayed hypersensitivity reactions and the rising rate of antibiotic resistance are becoming great challenges faced by many dermatologists today. This narrative review provides an overview of the main topical antibiotics used in dermatology, focusing on their clinical role in the most common dermatological indications. For this purpose, a review of MEDLINE and PubMed for pertinent, scientific, and clinical publications until March 2020 was performed. Only articles published in the English language were included.